2022
DOI: 10.1093/bjsopen/zrac070
|View full text |Cite
|
Sign up to set email alerts
|

Tamponade dressing versus no dressing after haemorrhoidectomy: multicentre, randomized clinical trial

Abstract: Background Symptomatic haemorrhoids are a common anorectal disorder. The aim of the study was to investigate whether the omission of tamponade dressings after haemorrhoidectomy reduces postoperative pain without increasing the risk of severe bleeding. Method This was an open-label, randomized clinical trial conducted at 14 German hospitals. All patients with third- or fourth-degree haemorrhoids undergoing haemorrhoidectomy we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Langenbach et al also conducted a large-sample study comparing tamponade dressing and no dressing after hemorrhoidal surgery. This study revealed that post-operative pain scores were lower in the no dressing group during the first 6–12 h post-surgery than in the tamponade dressing group; however, the use of analgesics was similar in both groups 14 . In this study, the reduction in pain but not in the use of analgesics may be attributed to the fact that the difference in pain intensity between the two groups was only one point (from 6 to 5), which did not exceed the minimal clinically important difference 15 , 16 .…”
Section: Discussionmentioning
confidence: 60%
“…Langenbach et al also conducted a large-sample study comparing tamponade dressing and no dressing after hemorrhoidal surgery. This study revealed that post-operative pain scores were lower in the no dressing group during the first 6–12 h post-surgery than in the tamponade dressing group; however, the use of analgesics was similar in both groups 14 . In this study, the reduction in pain but not in the use of analgesics may be attributed to the fact that the difference in pain intensity between the two groups was only one point (from 6 to 5), which did not exceed the minimal clinically important difference 15 , 16 .…”
Section: Discussionmentioning
confidence: 60%